Education and digital competencies of elder adults - Orłowska, Małgorzata; Błeszyńska, Krystyna M. (Kultura-Społeczeństwo-Edukacja, 2020)
The next decade was announced by WHO as the Decade of Healthy Aging. This is the answer to the social issue of highly developed countries, which is the aging of the society. In this context, there is the problem of active participation of seniors in social life, and especially the prevention of their social marginalization. Hence, projects that counteract exclusion and support active aging processes largely refer to modern technologies. Searching for answers to these questions and dilemmas, this text adopts an interdisciplinary approach, situating undertaken analyzes in the context of theories of aging, motivation as well as learning and using new technologies. The conclusions of the research undertaken – theoretical and empirical studies – undermine the hypothesis of digital exclusion of seniors perceived as the age group category. In the light of this research, it seems that education is the factor that influences the development of digital divide and digital inequalities within the community.